2017
DOI: 10.1111/geb.12680
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity, infrequent major host switching and the diversification of highly host‐specific symbionts: The case of vane‐dwelling feather mites

Abstract: Aim Highly host‐specific symbionts are very rarely found except with their typical host species. Although switches to new hosts are rare and difficult to detect, a switch to a host phylogenetically distant from the original one (a ‘major host switch’) could allow diversification of the symbionts onto the new host lineage. The consequences of such major host switches on the diversification of highly host‐specific symbionts of animals have rarely been explored. Here, we examine the host specificity of vane‐dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 83 publications
5
55
0
1
Order By: Relevance
“…Lack of bird–feather mites phylogenetic congruence (at low taxonomic ranks) and the power of host‐switching to trigger further diversification have been shown elsewhere (Doña, Sweet, et al, ; Doña, Proctor, Mironov, et al, ; Matthews et al, ), and here, we provide evidence on how these patterns emerge from processes occurring at ecological and microevolutionary scales. Perhaps more importantly, a highly dynamic ecoevolutionary scenario where macroevolutionary patterns are only one of its outcomes is depicted, demanding to focus on the dynamics of these unexpected associations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Lack of bird–feather mites phylogenetic congruence (at low taxonomic ranks) and the power of host‐switching to trigger further diversification have been shown elsewhere (Doña, Sweet, et al, ; Doña, Proctor, Mironov, et al, ; Matthews et al, ), and here, we provide evidence on how these patterns emerge from processes occurring at ecological and microevolutionary scales. Perhaps more importantly, a highly dynamic ecoevolutionary scenario where macroevolutionary patterns are only one of its outcomes is depicted, demanding to focus on the dynamics of these unexpected associations.…”
Section: Discussionsupporting
confidence: 81%
“…However, specifically, these hosts were more distantly related to the typical hosts than expected according to the phylogenetic host specificity of typical bird–feather mite associations (Figure ). And this degree of relatedness was partially overlapping with the longest phylogenetic distances reported for typical associations in Doña, Proctor, Mironov, et al () (Figure ). Finally, these unexpected associations were found in hosts with phylogenetic distances much shorter than potential associations with other bird species found in the same localities (e.g., mite species coming from non‐passerine birds of the study localities would have introduced hosts in the analysis which would have shown phylogenetic distances above 100 in Figure ).…”
Section: Discussionsupporting
confidence: 63%
“…Feather mite species are relatively host‐specific and (presumably) host‐specialized symbionts that appear to have relatively low levels of switching to new host species (Doña, Proctor, et al., ; Doña, Sweet, et al., ; Gaud ; Klimov, Mironov, & O'Connor, ; Matthews et al., ). These switches mostly involve closely related hosts, but major‐host switches (e.g., between bird orders) have been revealed as a major driver of their diversification (Doña, Proctor, et al., ). As for many other host–symbiont systems (Clayton, Bush, & Johnson, ; Nylin et al., ), understanding the (co)eco‐evolutionary scenario of host‐switching in this host–symbiont system is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all bird species harbour species‐ or genus‐specific feather mites (Doña, Proctor, Mironov, Serrano, & Jovani, ; Gaud & Atyeo, ; Proctor, ). Feather mites are highly specialized symbionts due to their (i) life cycle (i.e., they are permanent ectosymbionts, Dabert & Mironov, ; Proctor, ); (ii) high host specificity (Doña, Proctor, Mironov, Serrano, & Jovani, ); (iii) specific distribution on particular feathers and microsites on feathers (Fernández‐González, Pérez‐Rodríguez, de la Hera, Proctor, & Pérez‐Tris, ; Jovani & Serrano, , ; Stefan et al., ); and (iv) mainly vertical mode of transmission (Doña, Potti, et al., ; Jovani, Tella, Sol, & Ventura, ; Mironov & Malyshev, ). However, as with many other symbionts, they are challenging to study, and this has strongly hampered our comprehension of this system (Doña, Diaz‐Real, et al., ; Proctor, ; Proctor & Owens, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, to our knowledge, few studies of parasite host specificity across biogeographical scales account for variation in available hosts (Krasnov et al 2004, Cooper et al 2012, Lootvoet et al 2013, Doña et al 2017, Poisot et al 2017. Yet, to our knowledge, few studies of parasite host specificity across biogeographical scales account for variation in available hosts (Krasnov et al 2004, Cooper et al 2012, Lootvoet et al 2013, Doña et al 2017, Poisot et al 2017.…”
Section: Introductionmentioning
confidence: 99%